Waste Management through BSF Maggot Cultivation at the PGOT Mardi Utomo Semarang Social Rehabilitation Centre to Support Goal No. 12 of the SDGs - Siagian, Fanni (Sekolah Vokasi Universitas Diponegoro, 2024)
This study addresses the pressing issue of organic waste management at the PGOT Mardi Utomo Social Rehabilitation Centre in Semarang, Central Java. The centre, focused on social rehabilitation for individuals facing welfare challenges, grapples with the environmental impact of unmanaged organic waste. Through on-site observation and waste management service by students, this research advocates the use of maggots to transform organic waste into fertilizers. This innovative approach not only reduces waste volume but also yields high-quality organic fertilizers, fostering a renewable and eco-friendly environment. By embracing maggot technology, the rehabilitation centre can efficiently and sustainably address its organic waste challenge, contributing to achieving SDGs Goal 12.